Spatial pattern of changes in land surface temperature of seram island based on google earth engine cloud computing - Heinrich Rakuasa; Daniel Anthoni Sihasale; Philia Christi Latue (International Journal of Basic and Applied Science, 2023)
Monitoring land surface temperature in Seram Island using cloud computing-based geospatial technology, Google Earth Engine, could help to understand global climate and weather changes, and provide important information for scientists, governments, and non-governmental organizations to make decisions related to climate change mitigation and natural disaster management. This study aims to analyze the spatial pattern of land surface temperature change on Seram Island based on the cloud computing Google Earth engine. This research uses Moderate Resolution Imaging Spectroradiometer (MODIS) Terra Land Surface Temperature and Emissivity 8-day global satellite image data, which are accessed and analyzed in Google Earth Engine and Arc GIS. The results of this study show that the value of land surface temperature on Seram Island in 2017 is 14.7089ᵒC at the lowest value and 30.1012ᵒ C at the highest value and it increased in 2022 where the lowest temperature value is 14.0452ᵒC and the highest temperature is 32.639ᵒC. Built-up land and open land areas on Seram Island have very high surface temperature values compared to forests and plantations which have low land surface temperatures. Analysis of land surface temperature in Seram Island Regency could provide important information for the local government to make policies and plans for sustainable regional development